Titles in research and review articles in veterinary medicine : a corpus-based study - Gandur, Analía Mariela (2015)
Titles of research and review articles that satisfy the features of precision, information and easy-indexation require the mastering of certain linguistic and pragmatic skills from the researcher-writer. The mastering of this communicative competence exerts a demand especially on junior researchers at two important activities of their daily efforts: decoding and encoding titles when doing bibliographic searches and getting their own findings published. The purpose of this thesis work is to identify features, both linguistic and pragmatic, of research article (RA) and review article (RVA) titles in the field of Animal Production. The underlying hypothesis is that the titles of both genres will present structures with distinctive features. I expect that their identification will reveal particular features of the language of titles from these two scientific genres and the pragmatic functions that accord to the purposes of scientists in Animal Production, as well as how these features and functions may realize a well-written title. The study was based on a corpus of 480 titles, out of which 300 were RAs and 180 were RVAs, from prestigious international journals in electronic form from the period 2008-2011. Title length and lexical density were analyzed in the titles of the structures considered, namely noun phrase, compound construction, statements and questions. Heads in all structures, and pre and post modification in one-head noun phrase titles were analyzed, as well as the structures and pragmatic functions at both sides of the colonic titles. The results evidence some genre and discipline peculiarities worth considering for pedagogical purposes.